Financialization and corporate downsizing as a shareholder value strategy. (19th July 2021) - Jung, Jiwook; Lee, Yin
Abstract: How has financialization contributed to the changing nature of employment relations? Using the case of downsizing, we provide a cultural explanation of how the growing influence of the financial sector has reshaped employment relations at non-financial firms. We focus on the role of financial professionals in promoting the norm of shareholder value maximization around which financial market expecatations are formed and imposed upon firms. Our analysis of downsizing announcements made by the largest US firms shows that firms downsize when they miss earnings forecasts of securities analysts—a clear indication that firms fail to maximize shareholder value. We also show that institutional investors and financial executives promoted downsizing after missed analyst forecasts while labor unions resisted it. Despite the latter group's resistance, in the context of the declining countervailing influence of labor, our findings suggest that downsizing has become institutionalized as a shareholder value strategy in the era of financialization.